KEMISKINAN DAN BEBAN KERJA PEREMPUAN DI LERENG MERAPI SELATAN - Hastuti Hastuti (Jurnal Penelitian Humaniora, 2004)
Abstract The aim of this research is to  know the poetry and jobs load of women. The method used in research population survey by using 83 respondents consisting of household with husband and wife in area investigation. While the analysis techniques used descriptive quantitative include frequency table analysis. The research area is in Kalitengah Lor village, Glagahhardjo, Cangkringan, Sleman. The data collected were processed using descriptive analysis, percentage, and frequency table and cross tabulation. The research shows that today women start to work at public sector although they still also have to keep their domestically sector, so that women’s jobs are getting more hard. It seems that this is the consequence of women who choose to work at public sector. The demand of life need which is getting more and more stick and variety force the women to work and get some money to fulfill the life need. Although the women work in public sector reliable source of income with largest contribution in household income, household living condition which are still below the poverty. Keywords: poverty and jobs load of women